(3GdYbGFO GdfSajIs - (3YeQ Hf eMeO Hf CMeO Hf ESeGYjd, CHh MaU, fLe GdOjf GdfSaj,J (B537 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje bGd Cgd GdMb MbGFb GdCTjGA KGHJg hGdYde HgG JMbb NdGakG ddShaSWGFjI hCSHGH GdYde ddNdb KdGKI GdMhGS GdSdjeI hGdNHQ hGdUGOb hGdYbd s
(3BNQgG (B:s
(3hGdeLJgO bO jNWF hjUjH hQSd GdHTQ GaVd ef QSd GdedGFcI hQSd GdeQGFcI CaVd ef YGeI GdHTQ hYGeI GdHTQ CaVd ef YGeI GdedGFcI , hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B306 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B783s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1145s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJhMjO hGdedd hGdfMds